Influence of photons of the near-ultraviolet radiation on the growth and development of sugar beet (Beta vulgaris L. ssp. vulgaris var. saccharifera Alef.) in a closed agrobiotechnosystem - V. V. Latushkin; V. N. Zelenkov; A. A. Kosobryukhov; V. B. Novikov; L. N. Putilina; M. I. Ivanova; P. A. Vernik; S. V. Gavrilov (Овощи России, 2023)
Relevance and methodology. In order to determine the effect of near-ultraviolet radiation with a wavelength of 380 nm on the growth and development of a sugar beet hybrid plant, Smena was grown for 82 days under LED lighting with phytolamps and under conditions of increased UV-A intensity of the light range (an increase in the UV/PPFD ratio (0.027) compared with the control (0.0075) while maintaining the ratio of the remaining sites spectrum). The study was carried out on the basis of the digital software package "Synergotron" with a controlled internal environment.Results. An increase in the share of UV-A in the illumination spectrum leads to a significant change in the biometric indicators of plants – the aboveground biomass increases by 2.2 times compared to the control, and the mass of the underground part (root crops), on the contrary, decreases by 86.9%. At the same time, the share of root crops in the total biomass of plants decreases from 60% in the control to 30%. The morphological structure of the leaf apparatus changes: the proportion of petioles increases significantly compared to leaf blades (64.8% of petioles in aboveground biomass, whereas in the control 30%). Probably, an increase in the share of UV-A in the spectrum can favorably affect the cultivation of leaf forms of beets and other root crops. UV-A radiation leads to a change in the chemical composition of root crops, in particular, a decrease in the accumulation of dry substances (by 1.58%) and a decrease in sugar content (by 1.8%). An increase in the proportion of UV-A in the irradiation spectrum changes the parameters of chlorophyll fluorescence and contributes to an increase in the maximum quantum yield of Fv/Fm, non-photosynthetic quenching of NPQ fluorescence and a decrease in the real quantum yield of photosynthesis Y(II), as well as the electron transport rate (ETR).